Transverse Sinus Stenosis in Venous Pulsatile Tinnitus Patients May Lead to Brain Perfusion and White Matter Changes - Li, Xiaoshuai; Xu, Ning; Meng, Xuxu; Dai, Chihang; Qiu, Xiaoyu; Ding, Heyu; Lv, Han; Zeng, Rong; Xie, Jing; Zhao, Pengfei; Yang, Zhenghan; Gong, Shusheng; et al. (Frontiers in Neuroscience, 2021)
Objective: Transverse sinus stenosis (TSS) is associated with various symptoms, but whether it can lead to pathological brain changes is unclear. This study aimed to investigate brain changes in venous pulsatile tinnitus (PT) patients with TSS. Materials and Methods: In this study, fifty-five consecutive venous PT patients and fifty age- and gender-matched healthy controls (HCs) were investigated. In CT venography, the combined conduit score (CCS) was used to assess the degree of TSS in venous PT patients. Magnetic resonance venography was used to assess TSS in HCs. All the participants had undergone arterial spin labeling and structural MRI scans. Results: Two patients without TSS and ten HCs with TSS were excluded. Fifty-three venous PT patients with TSS and 40 HCs without TSS were included in this study. All the patients had unilateral cases: 16 on the left and 37 on the right. Based on the CCS, the patients were divided into high-degree TSS (a score of 1-2) (n = 30) and low-degree TSS groups (a score of 3-4) (n = 23). In the whole brain and gray matter, the patients with high-degree TSS showed decreased cerebral blood flow (CBF) compared with patients with low-degree TSS as well as HCs (P < 0.05), and no significant difference in CBF was found in patients with low-degree TSS and HCs (P > 0.05). In white matter (WM) regions, the patients with high-degree TSS exhibited decreased CBF relative to the HCs (P < 0.05). The incidence of cloud-like WM hyperintensity was significantly higher in the above two patient groups than in the HC group (P < 0.05). Conclusions: TSS in venous PT patients may lead to decreased CBF and cloud-like WM hyperintensity. These neuroimaging findings may provide new insights into pathological TSS in venous PT.